2018
DOI: 10.3349/ymj.2018.59.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Can Predict Vasculitis Activity and Poor Prognosis in Granulomatosis with Polyangiitis

Abstract: PurposeWe investigated whether red blood cell distribution width (RDW) predicts vasculitis activity based on Birmingham vasculitis activity score (BVAS) or BVAS for granulomatosis with polyangiitis (GPA) at diagnosis and poor prognosis during follow-up in patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV).Materials and MethodsWe reviewed the medical records of 150 patients with AAV. We defined severe GPA as BVAS for GPA ≥7 (the highest quartile). Correlation and standardised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, NLR also played a positive role in renal damage, and a higher baseline NLR led to a worse renal prognosis ( 45 ). RDW is a routine measurement of the heterogeneity of circulating red blood cell size and is clinically used to distinguish different types of anemia, especially iron-deficiency anemia and chronic anemia ( 46 ). Kim et al found that RDW≥15.4% at diagnosis might increase the risk of severe GPA and predict refractory disease type ( 46 ), and this might be related to the presence of a large number of pro-inflammatory factors in patients with AAV during disease activity, while pro-inflammatory factors were associated with the development of anemia in various diseases ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NLR also played a positive role in renal damage, and a higher baseline NLR led to a worse renal prognosis ( 45 ). RDW is a routine measurement of the heterogeneity of circulating red blood cell size and is clinically used to distinguish different types of anemia, especially iron-deficiency anemia and chronic anemia ( 46 ). Kim et al found that RDW≥15.4% at diagnosis might increase the risk of severe GPA and predict refractory disease type ( 46 ), and this might be related to the presence of a large number of pro-inflammatory factors in patients with AAV during disease activity, while pro-inflammatory factors were associated with the development of anemia in various diseases ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al ( 27 ) indicated that RDW was increased in patients with TA with anemia compared with patients with TA without anemia and control subjects, which was consistent with the present study. However, Kim et al ( 30 ) indicated that RDW was not significantly associated with HB, which may be related to the sex and age variations between the enrolled cohorts.…”
Section: Discussionmentioning
confidence: 93%
“…Among three subtypes of AAV, RDW at diagnosis could estimate the current activity of GPA and also, predict refractory disease of GPA during follow-up. 60 Next, as for indices containing two to four variables of the initial routine laboratory tests, CRP/serum albumin ratio (CAR) is a formula using two acute-phase reactants that are in the reciprocal direction. CAR at diagnosis was calculated in 170 Korean AAV patients in both SHAVE and retrospective cohorts.…”
Section: Serological Indices In Korean Patients With Aavmentioning
confidence: 99%